Spiking Neurons Integrating Visual Stimuli Orientation and Direction Selectivity in a Robotic Context - Cyr, André; Thériault, Frédéric; Ross, Matthew; Berberian, Nareg; Chartier, Sylvain (Frontiers in Neurorobotics, 2018)
Visual motion detection is essential for the survival of many species. The phenomenon includes several spatial properties, not fully understood at the level of a neural circuit. This paper proposes a computational model of a visual motion detector that integrates direction and orientation selectivity features. A recent experiment in the Drosophila model highlights that stimulus orientation influences the neural response of direction cells. However, this interaction and the significance at the behavioral level are currently unknown. As such, another objective of this article is to study the effect of merging these two visual processes when contextualized in a neuro-robotic model and an operant conditioning procedure. In this work, the learning task was solved using an artificial spiking neural network, acting as the brain controller for virtual and physical robots, showing a behavior modulation from the integration of both visual processes.